1999
DOI: 10.1274/jmor.16.148
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Androgens on Early Development of Mouse Follicles in Organ-Cultured Ovaries.

Abstract: Abstract:Ovaries from 4-day-old mice were organ-cultured and the effects of progesterone, androstenedione and estradiol-17β on early follicular development were investigated. Both androstenedione (40-1,000 ng/ml) and estradiol-17β (8-1,000 ng/ml) promoted proliferation of granulosa cells in developing follicles, while progesterone showed no remarkable effect. Cyproterone acetate (4,000 ng/ml), an androgen receptor antagonist, partially inhibited the granulosa cell proliferation induced by androstenedione (40 n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2012
2012

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Besides the factors described above, estradiol [66] and androstenedione [67,68] are potent stimulators of follicular growth in vitro. IGF-I also enhances granulosa cell proliferation, maintenance of follicular integrity, and the survival of oocytes in vitro [29,32].…”
Section: Medium Supplements Affecting Granulosa Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides the factors described above, estradiol [66] and androstenedione [67,68] are potent stimulators of follicular growth in vitro. IGF-I also enhances granulosa cell proliferation, maintenance of follicular integrity, and the survival of oocytes in vitro [29,32].…”
Section: Medium Supplements Affecting Granulosa Cellsmentioning
confidence: 99%
“…Besides FSH, antral formation of mouse preantral follicles is promoted by the addition of dbcAMP [69] and androstenedione [67,68] to the medium. Activin A has also been shown to promote follicular antrum formation in the rat [70] and humans [35].…”
Section: Medium Supplements Affecting Antrum Formationmentioning
confidence: 99%
“…Furthermore, androgens directly promote the growth and antral formation of mouse pre-antral follicles in vitro . Similarly, in organ-cultured ovaries isolated from 4-day-old mice, androstenedione induced proliferation of granulosa cells (Ikeda et al 1999). Moreover, both studies confirmed the promotional effect of dihydrotestosterone, which does not convert to estrogens.…”
Section: Steroidsmentioning
confidence: 53%
“…1998). Similarly, in organ‐cultured ovaries isolated from 4‐day‐old mice, androstenedione induced proliferation of granulosa cells (Ikeda et al . 1999).…”
Section: Culture Conditionsmentioning
confidence: 96%
“…Although some positive effects of activin A on preantral follicle growth have been reported [28,35,74], impaired follicle viability because of activin A treatment has also been reported [75]. Estradiol [13] and androstenedione [76,77] are other potent stimulators of follicular growth in vitro that will be discussed later.…”
Section: Granulosa Cellsmentioning
confidence: 98%